History of science, philosophy, and culture in Indian civilization : Vol. 8, pt. 3 : Economic history of India from eighteenth to twentieth century - Chaudhuri, B. B. (New Delhi : Project of History of Indian Science, Philosophy and Culture, 2005)
Contributed articles.
Includes bibliographical references and index.
Keywords: India -- Economic conditions -- 18th century; India -- Economic conditions -- 19th century; India -- Economic conditions -- 20th century